Compensation of Corn Yield Components to Late‐Season Stand Reductions in the Central and Northern Great Plains. (1st March 2017) - Haag, Lucas A.; Holman, Johnathon D.; Ransom, Joel; Roberts, Tom; Maxwell, Scott; Zarnstorff, Mark E.; Murray, Leigh
Abstract : Core Ideas: Plasticity of remaining yield components can reduce the impact of late season stand losses. Stand reductions as late as V14 did not result in 1:1 yield losses. The relative importance of yield component compensation varied by timing and location/hybrid. Hail insurance adjustment procedures for corn ( Zea mays L.) in the United States prior to 2014 assumed that yield reductions from V9 through milk stage were linear with stand reduction on a percentage basis. Other research suggests that corn plants retain some level of yield plasticity past the V9 growth stage. Some methods of estimating yield reductions may not be appropriate for modern hybrids and management practices. Field trials were conducted in the central Great Plains near Garden City, KS, in 2008, 2009, and 2011 and the northern Great Plains near Prosper, ND, in 2008 to 2010. Corn stands were reduced in a factorial of rates (0, 25, 50, and 75%) and timings (V5, V8, V11, and V14). Grain yields declined 17.2% at Garden City and 10.7% at Prosper as the timing of stand reduction progressed from V5 to V14. Yield declined 57.7% at Garden City and 54.2% at Prosper as the rate of reduction increased from 0 to 75%. The relative importance of ears plant −1, kernels ear −1, and kernel weight varied with timing of stand reduction. Grain yields were not reduced on a 1:1 basis by stand reductions occurring at V11 and V14. The yield plasticity of remaining plants at V11 was similar to that at V8. The results suggest that adjustment procedures for late season stand reductions, especially near V11, need to adequately reflect plasticity in corn yield components.